2004
DOI: 10.1089/end.2004.18.527
|View full text |Cite
|
Sign up to set email alerts
|

Results of Shockwave Lithotripsy for Pediatric Urolithiasis

Abstract: Employing a strict definition of treatment success, single-session SWL in our series offers moderate efficacy in the pediatric population. Patients who have a large stone or risk factor such as an anatomic abnormality are less likely to become stone free and might better undergo an endourologic procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…A study by Tan,  et al . reported only moderate efficacy of ESWL in the pediatric population [23]. He documented 100 patients with a mean stone size of 7.8 mm, where 60% of the patients were declared as stone cleared after the first extracorporeal shock wave lithotripsy session, and the stone-free rate amplified to 68% after a second session.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Tan,  et al . reported only moderate efficacy of ESWL in the pediatric population [23]. He documented 100 patients with a mean stone size of 7.8 mm, where 60% of the patients were declared as stone cleared after the first extracorporeal shock wave lithotripsy session, and the stone-free rate amplified to 68% after a second session.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that harmful effects of shock waves of ESWL can be avoided only by decreasing the number of shockwaves and reducing the energy in kilovolts [20]. Many studies have documented that there are no deleterious effects of ESWL on flourishing kidneys [21-23]. Considering the fact that we are still awaiting long-term data, it would seem prudent to shock the pediatric kidney as little as possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, urologic intervention may be necessary if the calculus does not progress or spontaneously pass within 30 days (7). Additionally, complications may occur up to 3 months after the stone has been identified, suggesting that follow-up longer than 30 days may be necessary (8).…”
Section: Introductionmentioning
confidence: 99%
“…The frequent failure of ESWL in children, however, is primarily associated with anatomical abnormalities of the kidney and urinary tract malformations. According to some authors, they reduce the chance of plaque removal after the first session from 64 to 31% [18, 19]. …”
Section: Discussionmentioning
confidence: 99%